2013
DOI: 10.1590/s0100-69912013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de doentes esofagectomizados: adenocarcinoma versus carcinoma epidermoide

Abstract: OBJETIVO: Avaliar e comparar a qualidade de vida de pacientes esofagectomizados para tratamento de adenocarcinoma da junção esofagogástrica e de carcinoma epidermoide. MÉTODOS: estudo transversal no pós-operatório de doentes esofagectomizados por adenocarcinoma da junção esofagogástrica (Adenoca) e carcinoma epidermóide (CEC), empregando o questionário SF-36 aplicado em 24 pacientes (10 por Adenoca e 14 por CEC), a partir do 5º mês de pós-operatório, incluindo os sintomas clínicos e a variação de peso. RESULTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…In a study conducted in Rio Grande do Sul (9) , with a total of 41 patients, it was shown that role performance is the function that most affects quality of life, since it was found in a lower score (64.61), showing that patients may have difficulty in performing leisure and work activities. In another study, 24 esophagectomy patients were analyzed in which, when comparing the quality of life of the two histological types of esophageal cancer, there was a significant difference in the domain of functional capacity and equality in all other domains (4) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted in Rio Grande do Sul (9) , with a total of 41 patients, it was shown that role performance is the function that most affects quality of life, since it was found in a lower score (64.61), showing that patients may have difficulty in performing leisure and work activities. In another study, 24 esophagectomy patients were analyzed in which, when comparing the quality of life of the two histological types of esophageal cancer, there was a significant difference in the domain of functional capacity and equality in all other domains (4) .…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring can be aimed at patient adherence to treatment, in addition to being an important tool in their self-management. Thus, nurses are responsible to establish education strategies, leading to safety, promoting clear and effective communication, aiming to improve treatment and home care after a surgical procedure (2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nos primeiros meses de pós-operatório, os pacientes podem apresentar sintomas indesejáveis, como pouca aceitação alimentar, náuseas, perda de peso, astenia, diarreia, dor, disfagia e regurgitação que podem prejudicar a qualidade de vida quando comparada à condição pré-operatória 15 .…”
Section: Introductionunclassified